2016
DOI: 10.1002/pbc.26017
|View full text |Cite
|
Sign up to set email alerts
|

Transfusional Iron Overload in a Cohort of Children with Sickle Cell Disease: Impact of Magnetic Resonance Imaging, Transfusion Method, and Chelation

Abstract: BackgroundTransfusions prevent a number of complications of sickle cell disease (SCD), but cause inevitable iron loading. With magnetic resonance imaging (MRI), liver iron can be monitored noninvasively. Erythrocytapheresis can limit iron loading and oral chelation provides a more tolerable alternative to subcutaneous administration. The impact of these factors on control of iron burden in SCD has not been well studied.ProcedureIron monitoring practices, chelation use, and transfusion methods were assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
1
23
2
Order By: Relevance
“…reported relatively stable ferritin concentrations in children receiving MET, whereas Stanley et al. found that aRBCX recipients had a greater LIC reduction than simple transfusion recipients, measured by MRI . Although we did not find a significant difference in serum ferritin between the aRBCX and MET groups, we found that children who had a chelation holiday received a greater percentage of their transfusion therapy by aRBCX, and were more adherent to appointments and chelation therapy.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…reported relatively stable ferritin concentrations in children receiving MET, whereas Stanley et al. found that aRBCX recipients had a greater LIC reduction than simple transfusion recipients, measured by MRI . Although we did not find a significant difference in serum ferritin between the aRBCX and MET groups, we found that children who had a chelation holiday received a greater percentage of their transfusion therapy by aRBCX, and were more adherent to appointments and chelation therapy.…”
Section: Discussioncontrasting
confidence: 88%
“…23 Savage et al 24 and Aloni et al 25 reported relatively stable ferritin concentrations in children receiving MET, whereas Stanley et al found that aRBCX recipients had a greater LIC reduction than simple transfusion recipients, measured by MRI. 26 Although we did not find a significant difference in serum ferritin between the aRBCX and MET groups, we found that children who had a chelation holiday received a greater percentage of their transfusion therapy by aRBCX, and were more adherent to appointments and chelation therapy. Our results suggest that patient factors, including adherence to the transfusion schedule and prescribed medications, may be as important in controlling Hb S and ferritin levels as the type of transfusion therapy employed.…”
Section: Discussioncontrasting
confidence: 72%
“…Iron overload is a common complication of simple transfusion regimens for chronic therapy . It is often severe enough to require iron chelation.…”
Section: Rbc Exchange Treatment Considerationsmentioning
confidence: 99%
“…It is often severe enough to require iron chelation. Because automated RBC exchange removes older RBCs from the patient's system, it is less likely to cause iron overload and may even reduce iron overload in patients who previously received treatment on a simple transfusion regimen . Patients who do not benefit from or are not compliant with iron chelation may be better served by being switched to automated exchange.…”
Section: Rbc Exchange Treatment Considerationsmentioning
confidence: 99%
“…If used as the initial form of transfusion, it may prevent iron overload and can allow cessation of iron chelation in well-chelated patients. 19,20 A small proportion of patients (particularly those with a low baseline Hb level) will accumulate iron at a low rate even with RCE and may need concurrent iron chelation at a reduced intensity. Automated exchanges do require more blood than manual exchange or simple transfusion but are not associated with increased rates of alloimmunization.…”
mentioning
confidence: 99%